Monocyte to high-density lipoprotein and apolipoprotein A1 ratios are associated with bone homeostasis imbalance caused by chronic inflammation in postmenopausal women with type 2 diabetes mellitus - Rong Huang; Yang Chen; Mei Tu; Wei Wang (Frontiers Media S.A., 2022)
Objective: Emerging evidences demonstrated that chronic inflammation can influence bone metabolism in type 2 diabetes mellitus (T2DM), leading to bone homeostasis imbalance. The aim of this study was to assess the correlations between novel pro-inflammatory indexes like monocyte to high-density lipoprotein (MHR), apolipoprotein A1 (MAR) ratios and bone mineral density (BMD), bone turnover markers in Chinese postmenopausal women with T2DM.Method: In this study, a total of 619 participants with complete data were included in the final analysis. Demographic and anthropometric information was collected. Biochemical parameters and bone turnover markers were determined by standard methods. BMD was measured by dual-energy x-ray absorptiometry. Correlation analysis and regression models were conducted to assess the associations between MHR, MAR and bone turnover markers, BMD. Multiple binomial logistic regression model was used to estimate the independent variables of MHR and MAR for osteoporosis.Results: Overall, the prevalence of osteoporosis was 38.3%. MHR and MAR were significantly correlated with C-terminal cross linking of type I collagen (β-CTX), L1-L4, femoral neck BMD and T scores. These correlations remained significant after adjustment for other confounding factors. Meanwhile, MHR and MAR were also significantly associated with higher odds of osteoporosis, the odds ratios (ORs) (95%CI) were 1.88 (1.49-2.38) and 2.30 (1.72-3.09) respectively. Furthermore, MHR and MAR seemed to have a good identifying value for osteoporosis. The area under the curve of MHR and MAR identifying osteoporosis were 0.791 (95% CI: 0.753-0.828) and 0.843 (95% CI: 0.809-0.877) respectively (p < 0.001). The optimal cut-off values of MHR and MAR were 4.53 × 108/mmol (sensitivity: 60.8%, specificity: 85.9%) and 4.74 × 108/g (sensitivity: 71.7%, specificity: 89.3%) respectively.Conclusion: MHR and MAR were significantly associated with osteoporosis. These two novel pro-inflammatory indexes may be ideal markers to reflect bone homeostasis imbalance caused by chronic inflammation in Chinese postmenopausal women with T2DM.